“Que des cendres” Negative Byzantinism as an Imperial Ideology - Csillag, Paul (I.S. MED. - Interdisciplinary Studies on the Mediterranean, 2025)
In this chapter, I will deconstruct negative Byzantinism by analyzing Abel-François Villemain’s historical novel Lascaris, ou les Grecs du Quinzième Siècle (1825). In French Romantic literature at the beginning of the nineteenth century, the Eastern Roman (or Byzantine) Empire symbolized imperial degeneration. As a special form of Orientalism or Mediterraneanism, negative Byzantinism served Latin Christians to belittle Orthodox believers. Western writers used fictionalized tales of the Byzantine Empire as historical analogies to indirectly criticize the allegedly Oriental habits of the nineteenth-century Greeks. As a cultural alternative to Byzantinism, they proposed (Phil-)Hellenism. According to Philhellenes like Villemain, the Greeks ought to honor their Hellenic, ancient heritage and not their Christian, medieval traditions. Since Western authors deemed themselves the heirs of ancient Hellas – because of their supposedly enlightened education and liberal politics – they claimed tutelage over the current Greeks in the form of a historically justified civilizing mission. In contrast, they described the Russian Empire as a poor imitation of degenerate Byzantium unfit to rule its Orthodox coreligionists. Villemain spearheaded this worldview with his novel Lascaris. With my analysis of his book, I will demonstrate how the author instrumentalized the notion of Byzantine degeneration and Hellenic progress to argue in favor of French imperialism in the Eastern Mediterranean. The deconstruction of negative Byzantinism and the unveiling of its imperialist connotations is vital for a better understanding of past and present representations of the Byzantine Empire in historiography and historical fiction.